CFD Codes efficiency case study: Ability to perform numerical simulations in the refrigerated compartment of a foodstuff transportation vehicle - Gaspar, Pedro Dinis (2004)
The purpose of the present work is to describe the ability of the advanced computer packages (CFD codes) to perform numerical simulations of general refrigeration engineering problems. The case study concerns the modelling of three-dimensional turbulent airflow with thermal buoyant effects and air temperature distribution in the refrigerated compartment of a perishable foodstuff transportation vehicle. The numerical predictions obtained with three commercial codes (PHOENICS, FLUENT and CFX) and an academic one are evaluated and compared with experimental data. The validation of the numerical results is analysed and the modelling capabilities, usage simplicity and user interface of each code are discussed.